Correction of Prominent Ears: Postauricular Muscle Relocation and Fibrofatty Tissue Excision. Issue 6 (September 2021) - Mehmet, Gunay Murat; Baklaci, Deniz
Abstract : Abstract: In this study, we modified the combined Mustarde and Furnas type otoplasty technique and evaluated the postoperative results of the patients for symmetry and complications. Eighty prominent ears in 42 patients who underwent otoplasty between January 2017 and April 2019 were included in this study. The authors determined the amount of postauricular subcutaneous tissue to be removed according to the shape of skin incision and relocated the postauricular muscle as an adjunct to the Mustarde and Furnas otoplasty technique. All patients were followed-up at least 12 months postoperatively. The patients were also evaluated for early postoperative complications (bleeding, hematoma, perichondritis, wound infection, and skin necrosis), late postoperative complications (asymmetry, hypertrophic scars, suture extrusion, and recurrence), and patient satisfaction using objective and subjective methods. Considering all the patients, early complications consisted of minimal low-flow bleeding (n = 4 ears/4 patients), hematoma (n = 1), and perichondritis (n = 1). Late complications consisted of suture extrusion (n = 2 ears/2 patients), hypertrophic scars (n = 2 ears/2 patients), and asymmetry (n = 1). None of the patients presented with wound infection or skin necrosis. Revision otoplasty was unilaterally performed in only 1 patient with the complaint of asymmetry. A natural-looking, adequate correction, and symmetric ear shape were achieved in all patients except 1. In terms of patient satisfaction, 38 of 42 patients evaluated the outcome as "very good, " 3 as "good, " and only 1 as "poor." Our modified technique produced very satisfactory results and reduced the postoperative complication and asymmetry rates, as well as eliminating recurrence. The authors recommend this simple and safe procedure with excellent outcomes. Abstract : Supplemental Digital Content is available in the text